Gambaran Faktor Kegagalan Laten dan Kegagalan Aktif pada Kecelakaan Transportasi Darat di Indonesia Tahun 2019 – 2021 - Khairina, Rahma Laili; Erwandi, Dadan (UI Scholars Hub, 2022)
Road transportation accidents are the eighth leading cause of death worldwide, reaching 1.35 million people annually (WHO, 2021). Data from the NTMC Korlantas Polri for 2019-2021 shows that the number of road transportation accidents in Indonesia is above 100 thousand every year. This study identifies latent and active failure factors contributing to Indonesia's land transportation accidents to determine the causes of accidents comprehensively. This study uses secondary data with 320,084 traffic accident case reports in 2019-2021 belonging to the NTMC Korlantas Polri. The method used is qualitative by analyzing based on the Swiss Cheese Model. The results of this study indicate latent failure factors in road transportation accidents in Indonesia in 2019-2021, namely the initial condition of the brake vehicle not functioning (5.7%), occurring on roads with suitable conditions (92.5%), occurring in sunny weather conditions ( 92.3%), and bright/clear lighting conditions (79.1%). Active failure factors in land transportation accidents in Indonesia in 2019 - 2021 are the age of drivers aged 22 – 29 years (15.7%), drivers with a senior high school education/equivalent (48.4%), drivers who do not have a driver's license (28.3 %), and drivers who are careless towards traffic from the front (19.0%).